Effect of Incorporation of Liver Protein Hydrolysate on Processing Characteristics of Fibre-Enriched Meat Loaves : doi: 10.5958/2581-6616.2021.00011.6 - Verma, Akhilesh K.; Chatli, Manish Kumar; Kumar, Pavan; Mehta, Nitin (Journal of Meat Science, 2022)
Present study was conducted for evaluation of effect of addition of porcine liver protein hydrolysates into formulation of  pork loaves at four different levels viz. Control (0% C), 0.09% LA (T1), 0.06% LT (T2) and 0.09% LP (T3) and compared  for different physico-chemical, instrumental texture and colour profile, and sensory quality attributes. Emulsion stability,  pH and cooking yield value varied significantly among hydrolysate added sample than control whereas, fat content  remained comparable amongst all groups. Products pH, moisture, ash, carbohydrate, energy content, cooking yield,  cooking loss, and moisture retention of pork loves varied significantly (P0.05) for both test and control.  Liver hydrolysate addition in pork loaves resulted in significant reduction in lightness (L*), yellowness (b*) and chroma  value whereas redness (a*) and hue value remained comparable among all groups. All attributes of textural profiles varied  significantly (P
Keywords: Meat loaves; Liver hydrolysate; Colour profile; Texture profile; Sensory attributes